Pengaruh Service Quality, Citra Koperasi, Tingkat Bagi Hasil terhadap Kepuasan Anggota pada KPRI “SEHAT” RSUD Prof. Dr. Margono Soekarjo Purwokerto - Annisa Apriliantika; Ragil Purnomo; Adi Wiratno (Jurnal Akuntansi dan Audit Syariah)
Cooperatives are economic institutions that aim for mutual welfare. This study aims to determine the effect of service quality, product image, and profit sharing rate on member satisfaction of KPRI "Sehat" Prof. Dr. Margono Soekarjo Purwokerto Hospital. The data collection method used in this study was a questionnaire with a sample size of 45 respondents. The analysis used used multiple regression analysis using SPSS version 24. The results showed that service quality (X1) had a positive effect on member satisfaction, the cooperative image variable (X2) had no effect on member satisfaction. The variable profit sharing rate (X3) has a positive effect on member satisfaction of KPRI "Sehat" Prof. Dr. Margono Soekarjo Purwokerto Hospital.